Proceedings of the Twenty-Eighth Annual ACM-SIAM Symposium on Discrete Algorithms 2017
DOI: 10.1137/1.9781611974782.52
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Memory-Efficient Algorithms for Evacuation Problems

Abstract: We study two classical flow over time problems that capture the essence of evacuation planning. Given a network with capacities and transit times on the arcs and sources/sinks with supplies/demands, a quickest transshipment sends the supplies from the sources to meet the demands at the sinks as quickly as possible. In a 1995 landmark paper, Hoppe and Tardos describe the first strongly polynomial time algorithm solving the quickest transshipment problem. Their algorithm relies on repeatedly calling an oracle fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
(70 reference statements)
0
23
0
Order By: Relevance
“…Such chain flows in a nonstandard chain decomposition may use a backwards arc with negative transit time. Based on this landmark paper [18], authors in [21] have also presented the quickest transshipment algorithm to determine the quickest transshipment as a convex combination of simple lex-max dynamic flows. Now, we are presenting the quickest partial arc reversal transshipment algorithm to get the quickest arrival of evacuees at in corresponding to the arc reversal capability.…”
Section: Arrival Of Evacueesmentioning
confidence: 99%
“…Such chain flows in a nonstandard chain decomposition may use a backwards arc with negative transit time. Based on this landmark paper [18], authors in [21] have also presented the quickest transshipment algorithm to determine the quickest transshipment as a convex combination of simple lex-max dynamic flows. Now, we are presenting the quickest partial arc reversal transshipment algorithm to get the quickest arrival of evacuees at in corresponding to the arc reversal capability.…”
Section: Arrival Of Evacueesmentioning
confidence: 99%
“…Roughly speaking, the evacuation problem is the problem of sending all the supplies to the sinks as quickly as possible. Hoppe and Tardos proved that this problem can be solved in polynomial time (see also for another polynomial‐time algorithm). Notice that although the bit length of Θ (i.e., ⌈log 2 Θ⌉) is bounded by a polynomial in the input size, Θ may not be bounded by a polynomial in the input size (more precisely, Θ has pseudo‐polynomial size).…”
Section: Dynamic Flowsmentioning
confidence: 99%
“…The goal of this problem is to find the minimum time limit Θ such that we can send all the supplies to the sinks within time Θ. It is known [17] that we can solve the evacuation problem in polynomial time (see also [23] for another polynomial-time algorithm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have shown how to efficiently construct a Maximum Dynamic s-t flow: a path decomposition is first applied to the solution of a static minimum cost flow obtained in the original network, then temporally repeated flows are sent among the decomposed paths as long as there is enough time left to reach the destination t within the time horizon. Novel problems find their roots right in the dynamic environment, for instance the Quickest Transshipment Problem and the Earliest Arrival Flow Problem where the exact time horizon of the process is not known a priori [15,16,17]. For a complete overview of dynamic problems we refer to Aronson [3], Kotnyek [18], Köhler et al [4], Skutella [19].…”
Section: Introductionmentioning
confidence: 99%